The short-range order and its influence on radiation stability of low-concentration Fe-Cr alloys - Petrenko, P.V.; Kulish, N.P.; Mel’nikova, N.A.; Grabovskii, Yu.E.; Busko, T.O. (Вопросы атомной науки и техники, 2021)
The analysis of the structural phase state of Fe-Cr low concentration solid solutions and steel 1X13, associated with the formation of short-range order (SRO) of various types in them has been performed at the mesoscopic level. A comparison of the SRO and swelling of alloys under irradiation was carried out. It was shown that there is a fairly good qualitative correlation between them. Проаналізовано на мезоскопічному рівні структурно-фазовий стан низькоконцентраційних твердих розчинів Fe-Cr та сталі 1Х13 у зв’язку з утворенням у них близького порядку різних типів. Проведено порівняння ступеня близького порядку та величини розпухання сплавів при опроміненні. Показано, що між ними має місце досить добра якісна кореляція. Проанализировано на мезоскопическом уровне структурно-фазовое состояние низкоконцентрационных твердых растворов Fe-Cr и стали 1Х13 в связи с образованием в них ближнего порядка различных типов. Проведено сравнение степени ближнего порядка и величины распухания сплавов при облучении. Показано, что между ними наблюдается довольно хорошая качественная корреляция.